REALISING THE POTENTIAL OF INFORMATION COMMUNICATION TECHNOLOGY (ICT) TO SUPPORT PEOPLE CHALLENGED BY ILLNESS OR DISABILITY TO MAINTAIN THEIR INDEPENDENCE - Johnston, Ian (Ревија за социјална политика/Journal of Social Policy, 2015)
This presentation charts the progress of ENS4Care, aninnovative project funded by the EU for 2 years from December 2013 to engage social and health care practitioners in collaboratively addressing challenges arising from a rapidly ageing population in many parts of Europe (Eurostat, 2014). Principal amongst such challenges are the increasing numbers of people living with long-term conditions, disabilities, non-communicable diseases (NCD) and chronic diseases and the decreasing percentage of the population active in the healthcare labour force to manage the delivery of patient-centric care (WHO, 2010).